T43. Fasciculation potentials in Amyotophic Lateral Sclerosis (ALS): Not so common as fibrillation potentials. (May 2018) - Ross, Mark; Burge, Miranda; Zuniga, Leslie A.; Halker, Rashmi; Smith, Benn; Muzyka, Iryna; Estephan, Bachir; Khoury, Julie
Abstract : Introduction: When EMG studies are performed for evaluation of suspected ALS, the El Escorial diagnostic criteria require fibrillation potentials to serve as evidence of lower motor neuron disease. The Awaji Criteria allow fasciculation potentials together with neurogenic motor unit potentials to serve as EMG evidence of lower motor neuron disease. Although the Awaji Criteria have been considered to facilitate the diagnosis of ALS by not requiring fibrillation potentials on EMG, the El Escorial Criteria for the diagnosis of ALS continue to serve as the most commonly used criteria for ALS clinical trials. Methods: A retrospective review of the Mayo Clinic Arizona EMG laboratory database was performed for patients with the diagnosis of motor neuron disease over a 2 year period. The clinical and EMG findings were reviewed in detail. Results: The EMG database review revealed 125 patients with a diagnosis of motor neuron disease. Review of records revealed the final diagnosis was ALS in 112 of these and 13 were diagnosed with other forms of motor neuron disease. The clinical and EMG findings were reviewed in detail. In the ALS patients, a total of 1844 muscles were studied by EMG which represents an average of 16.5 muscles studied per patient. Of the 1, 844 muscles studied, 649 were reported to show fasciculation potentials (34%) and 1067 showed fibrillation potentials (58%). None of the patients diagnosed with ALS had 0 muscles showing fibrillation potentials. However, 15 patients (12%) were reported to have 0 muscles showing fasciculation potentials. The number of ALS patients with 5 or fewer muscles showing fasciculation potentials was high at 54 (48%) compared to the number of ALS patients with 5 or fewer muscles showing fibrillation potentials, which was only 16 (14%). Conclusion: This retrospective review of EMG findings in ALS patients suggests that fasciculation potentials are not identified as often as fibrillation potentials. All patients with a final diagnosis of ALS had fibrillation potentials on their EMG study whereas 12% of patients with a final diagnosis of ALS did not have fasciculation potentials identified on their EMG study. Thus, absence of fasciculation potentials should not be considered an unusual circumstance in ALS patients or an argument against the diagnosis of ALS. In contrast, fibrillation potentials are an expected finding in patients with ALS and the absence of fibrillation potentials does provide a strong argument against the diagnosis of ALS.